2022
DOI: 10.1002/cjce.24426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post‐pyrolysis wash on biochar properties

Abstract: Washing biochar modifies its properties for use as a soil amendment. The important biochar properties for use as a soil amendment are hydrophilicity, adsorption, and stability. Biochar was obtained with intermediate pyrolysis at 400°C of three different feedstocks: woodchips, Bayview Flowers Digestate, and Storm Fisher Digestate biomass. A simple wash with an aqueous surfactant solution improved the properties of the biochar for soil amendment, with a non‐ionic surfactant combined with oxidizing hydrogen perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…A comprehensive understanding and optimization of these properties can significantly enhance biochar's effectiveness as a reliable and long-term C sink. Various factors, including the feedstock used, pyrolysis conditions, and post-treatment processes, influence the physicochemical properties of biochar [26][27][28]. In this section, we delve into the properties that are particularly relevant to biochar's potential for C sequestration.…”
Section: Physicochemical Properties Of Biochar and Indices For Carbon...mentioning
confidence: 99%
“…A comprehensive understanding and optimization of these properties can significantly enhance biochar's effectiveness as a reliable and long-term C sink. Various factors, including the feedstock used, pyrolysis conditions, and post-treatment processes, influence the physicochemical properties of biochar [26][27][28]. In this section, we delve into the properties that are particularly relevant to biochar's potential for C sequestration.…”
Section: Physicochemical Properties Of Biochar and Indices For Carbon...mentioning
confidence: 99%
“…[ 31 ] Previous work indicated differences in the composition and surface chemistry of biochar from BFD and WCP. [ 43 ] This contributed to the observed differences in the yield and strength of granules created from unwashed biochar.…”
Section: Discussionmentioning
confidence: 99%
“…This changed the biochar from very hydrophobic to only slightly to moderately hydrophobic. [ 43 ] As shown in Table 3, the molasses binder solutions penetrated the bed of washed biochar from WCP within 3 to 4 s, indicating that this washed WCP biochar was only slightly hydrophobic. The penetration times ranged from 8 to 25 s for the washed biochar from BFD; these long penetration times indicated that this washed BFD biochar remained moderately hydrophobic.…”
Section: Discussionmentioning
confidence: 99%
“…The deashing of lignite has the ability to remove the minerals and ash under 0.5% making it environment-friendly and further suitable for higher adsorption of N by enhancing microporosity and surface area. The acid leaching of lignite also removed the potential contaminants, including volatile organic compounds, polyaromatic hydrocarbons, heavy metals, etc . Moreover, lignite is pathogen free; therefore, it is not as potentially dangerous as a soil amendment instead it improves the physical, chemical, and biological properties of soil and increases water retention capacity .…”
Section: Introductionmentioning
confidence: 99%